Development of Neuro-cognitive Module for Brain awareness program in Primary school in Sarawak - Fauzan, Norsiah; Nasir, Nurul Atikah (2017)
The development of Neuro-Cognitive Module is meant for the transfer of knowledge of neuroscience among the primary schools in sarawak. The learning modul consisting of three units such as Brain basics, sensing and movement will be developed to be transformed into video and uploaded in the MOOC for the outreached children in the rural area.